Optimasi Rute Distribusi Ayam Broiler dengan Metode Nearest Neighbour: (Studi Kasus: di CV. Global Putra Swasembada) - Mulyadi, Agus; Meirizha, St. Nova; Fanuddin, Obbie; Jusnita, Jusnita; Ali Ardi, Hendri (Fakultas Teknik UMRI, 2024)
Global Putra Swasembada is a company that distributes broiler chickens with a market area in Pekanbaru City. During the distribution process, the vehicle still has remaining capacity, which should be used to load customer orders in other areas. So, the number of tours formed and the number of vehicles used increases, which results in high distribution costs. An effective and efficient distribution method is needed to optimize distribution routes. The research uses the nearest-neighbour method to determine new routes. The results show that the distance of the existing route, which was previously 151.3 km, became 128.8 km, saving 22.5 km. The previous number of vehicles using 4 to 3 optimal vehicles. After calculating the distribution costs, the company paid the cost of Rp. 28,590,800 became Rp. 21,744,000, then there is a reduction in costs of Rp—6,846,800 or 14% every month.